Obtenção de sílica biogênica em esponjas de água doce do gênero drulia coletadas no Rio Tapajós - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
Freshwater sponges, known in the Amazon as cauxí are found easily in rivers, lakes and streams of the region. These animals are aquatic invertebrates and are set mainly in the vegetations suffering pulses of flooding during the rainy season. The sponges belong to the phylum porifera, which features three classes: Calcarea, Demospongiae and Hexactinellid. The skeleton of these sponges consists of siliceous spicules, except those belonging to the class calcarea. In this way, the aim of this study was to obtain silica of freshwater sponges, using the technique of heat treatment muffle oven. The sponges were collected in the community of Pajuçara axis region-Fort in the municipality of Santarém, Pará. The material was pre-treated to remove impurities from the site collection and then calcined in muffle oven at temperatures of 400, 600, 800 and 1000° C to estimate the amount of organic material and determine the best temperature for extraction. The samples obtained at temperatures of 600° C and 1000° C were used for characterization techniques of xray diffraction (DRX) and x-ray fluorescence (FRX). The results of XRD showed typical characteristics of amorphous silica-rich difratogramas with a broad peak corresponding to the SiO2, Al2O3 and Fe2O3 phases as well. The results obtained by FRX showed that the percentages in dry basis for phases SiO2, Al2O3 and Fe2O3 were of 90,21; 4,43 and 3,40% (m/m) to the temperature of 600° C and 90,35; 4,53 and 3,20% for temperature of 1000° C, respectively, in addition to other oxides in smaller amounts
Keywords: Sílica biogênica; esponja de água doce; Obtenção de sílica; CNPQ:: CIÊNCIAS BIOLÓGICAS